2012
DOI: 10.1182/blood-2011-06-361709
|View full text |Cite
|
Sign up to set email alerts
|

Vav3 collaborates with p190-BCR-ABL in lymphoid progenitor leukemogenesis, proliferation, and survival

Abstract: Despite the introduction of tyrosine kinase inhibitor therapy, the prognosis for p190-BCR-ABL+ acute lymphoblastic leukemia remains poor. In the present study, we present the cellular and molecular roles of the Rho GTPase guanine nucleotide exchange factor Vav in lymphoid leukemogenesis and explore the roles of Vav proteins in BCR-ABL–dependent signaling. We show that genetic deficiency of the guanine nucleotide exchange factor Vav3 delays leukemogenesis by p190-BCR-ABL and phenocopies the effect of Rac2 defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 52 publications
5
53
0
Order By: Relevance
“…The PIM protein belongs to the Ser̸Thr protein kinase family, is involved in multiple signal transduction pathways and is highly expressed in several types of tumors, including lymphoma (19). In this study, the expression variation trends of BAX and Bcl-xL in Raji and Jurkat cells following treatment with As 2 S 2 were in accordance with previous studies (20)(21)(22), with the difference that BAX in Jurkat cells was reduced to a lower level compared to the control group (P<0.01). Kang et al (23) conducted a study on human cervical cancer cells and reported that the translocation of BAX and the phosphorylation of Bcl-2 were associated with cell apoptosis and the increased level of mitochondrial BAX coexisted with no or minimal change in the total amount of BAX.…”
Section: Discussionsupporting
confidence: 77%
“…The PIM protein belongs to the Ser̸Thr protein kinase family, is involved in multiple signal transduction pathways and is highly expressed in several types of tumors, including lymphoma (19). In this study, the expression variation trends of BAX and Bcl-xL in Raji and Jurkat cells following treatment with As 2 S 2 were in accordance with previous studies (20)(21)(22), with the difference that BAX in Jurkat cells was reduced to a lower level compared to the control group (P<0.01). Kang et al (23) conducted a study on human cervical cancer cells and reported that the translocation of BAX and the phosphorylation of Bcl-2 were associated with cell apoptosis and the increased level of mitochondrial BAX coexisted with no or minimal change in the total amount of BAX.…”
Section: Discussionsupporting
confidence: 77%
“…Of the three VAV proteins, VAV3 reportedly plays an important role in tumor development and metastasis [33]. Previous reports demonstrated that VAV3 overexpression was associated with poor prognosis in gastric cancer patients [34], and VAV3 knockdown impaired carcinogenesis in leukemia and gastric cancer [34,35]; however, VAV3 expression in ovarian cancer has not yet been reported. In the present study, we revealed that VAV3 was overexpressed in OSCs, and VAV3 regulated CSC activation and cancer cell proliferation by spheroid-forming and colony-forming assays.…”
Section: Discussionmentioning
confidence: 99%
“…20 The results of longer-term follow-up (median, 2 years) in both of the COMFORT studies indicated that ruxolitinib treatment confers a survival advantage over placebo and best available therapy. 27,28 …”
Section: Ruxolitinibmentioning
confidence: 99%